Plasma epigenomic profiling reveals treatment-emergent squamous transformation in prostate cancer - Karl Semaan; Rashad Nawfal; John Canniff; Hunter Savignano; Ji-Heui Seo; Stephanie E. Siegmund; Sarah J. Wu; Julia K. Rotow; Gwo-Shu Mary Lee; Razane El Hajj Chehade; Ze Zhang; Gunsagar S. Gulati; et al. (npj Precision Oncology)
Abstract Squamous transformation of prostate adenocarcinoma is a rare resistance mechanism in patients with advanced prostate cancer that impacts both prognosis and treatment. Herein, we profile circulating chromatin in serial plasma samples collected from a patient with metastatic prostate cancer that experienced squamous transformation. We detect dynamic changes in gene regulation from circulating chromatin reflecting the emergence of squamous differentiation, enabling non-invasive diagnosis and monitoring of this resistance phenotype, with potential therapeutic implications.